Penerapan Arbitrase Online dalam Penyelesaian Sengketa Transaksi E-Commerce - Abdul Halim Barkatullah (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research focuses on method of dispute resolution using online arbitration as online dispute resolution. This research character is analytical descriptive. Analysis method used in this research is qualitative method. The result of this research shows: First, online arbitration as one of the method of dispute resolution using online dispute resolution considered by e-commerce business actors as the best solution in resolving dispute in cyber world; Second, online arbitration in the practice faces juridical obstacle in some matters as follow: (1) agreement to perform arbitration; (2) choice of arbiter (3) fulfillment of fundamental procedures; (4) character and execution of arbitration binding decision.Key words : Online arbitration, dispute, and e-commerce